2020
DOI: 10.2196/18306
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Listening to Understand the Lived Experience of Presbyopia: Systematic Search and Content Analysis Study

Abstract: Background Presbyopia is defined as the age-related deterioration of near vision over time which is experienced in over 80% of people aged 40 years or older. Individuals with presbyopia have difficulty with tasks that rely on near vision. It is not currently possible to stop or reverse the aging process that causes presbyopia; generally, it is corrected with glasses, contact lenses, surgery, or the use of a magnifying glass. Objective This study aimed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 27 publications
1
41
0
3
Order By: Relevance
“…A recent social media listening study found that individuals with presbyopia experienced difficulties with reading and electronic devices, and felt inconvenienced by the use of varifocal glasses and contact lenses. 76 An online survey of pre-presbyopic and presbyopic volunteers perceived comfort and convenience of their optical correction as more important than cost, with spectacles preferred over multifocal contact lenses for near vision correction. 77 Multifocal IOLs have been shown to improve patients’ quality of life, in contrast to patient satisfaction following presbyopic LASIK, which was found to be similar to reading glasses.…”
Section: Unmet Needs Of Presbyopic Patientsmentioning
confidence: 99%
“…A recent social media listening study found that individuals with presbyopia experienced difficulties with reading and electronic devices, and felt inconvenienced by the use of varifocal glasses and contact lenses. 76 An online survey of pre-presbyopic and presbyopic volunteers perceived comfort and convenience of their optical correction as more important than cost, with spectacles preferred over multifocal contact lenses for near vision correction. 77 Multifocal IOLs have been shown to improve patients’ quality of life, in contrast to patient satisfaction following presbyopic LASIK, which was found to be similar to reading glasses.…”
Section: Unmet Needs Of Presbyopic Patientsmentioning
confidence: 99%
“…Indeed, the social networks’ web monitoring approach has been suggested to be helpful to better understand some clinical and psychopharmacological issues related to a range of novel psychoactive substances (NPS) [ 35 ]. This approach has been recently referred to as “social media listening” [ 36 , 37 ], with the resulting findings providing insight into how people discuss their condition online. This research approach is, however, being combined with qualitative research for added rigour and confirmation of relevance of the related findings, i.e., triangulation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been recently referred to as “social media listening” [ 36 , 37 ], with the resulting findings providing insight into how people discuss their condition online. This research approach is, however, being combined with qualitative research for added rigour and confirmation of relevance of the related findings, i.e., triangulation [ 37 ]. Over the years, netnography, a qualitative, interpretative research methodology that adapts traditional ethnographic techniques to the study of online (e.g., social media; web) data [ 38 ] has increasingly been used as a strictly observational, unobtrusive approach in a range of health research fields, including pro-anorexia [ 39 ] and diabetes mellitus online peer support [ 40 ] communities.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing prevalence of presbyopia 2 stands to account for significant financial burden 8 while negatively impacting patients' quality of life and daily living.- 10,11 As well, loss of functional through focus is a safety concern. 12 However, what may be under appreciated is that some treatments also introduce safety concerns, 38 with substantial implications for direct medical costs. 23 Thus, a more meaningful comparison of treatment options based on an understanding of the optical principles leveraged by a given intervention would bring the clinician closer to understanding the true goal of correcting https://doi.org/10.2147/OPTH.S318065…”
Section: Discussionmentioning
confidence: 99%
“… 8 With increasing longevity, most people in the western world will spend almost half of their lives as presbyopes. 9 It is a condition that results in loss of productivity and quality of life, 10 , 11 and may create safety concerns, 12 suggesting it should be treated as an important medical need rather than as a lifestyle decision.…”
Section: Introductionmentioning
confidence: 99%